Strategic Development of Local Coffee SMEs: A Force Field Analysis of Growth Drivers and Constraints - Lady Hatita Breby Perangin Angin; Muhammad Irfan; Nira Dewi Susanti; Indrayani Indrayani (Journal of Marketing Management and Innovative Business Review, 2026)
This study aims to analyze the strategic development of local coffee SMEs in Balikpapan using a Force Field Analysis (FFA) approach to identify growth drivers and constraints. A qualitative-descriptive design was employed, with data collected through in-depth interviews, observations, and documentation from selected SME actors and stakeholders. The analysis reveals that the total weighted score of driving forces (6.87) exceeds restraining forces (5.58), indicating a positively inclined but fragile growth condition. Key driving forces include increasing coffee consumption and the availability of digital marketing platforms, while major constraints consist of limited access to capital and weak managerial capability. The findings highlight a critical growth–capability gap, where strong market opportunities are not fully supported by internal readiness. This study contributes by demonstrating the usefulness of FFA in capturing the dynamic interaction between enabling and constraining factors, offering more actionable insights compared to linear approaches. The results suggest that strengthening internal capabilities and optimizing digital adoption are essential to achieving sustainable growth. The study provides practical implications for SME actors and policymakers in formulating targeted development strategies.